NEW FINDINGS OF HOVERFLY FAUNA (DIPTERA: SYRPHIDAE) OF THE WESTERN PART OF SERBIA (ZLATIBOR AND RAŠKA DISTRICTS) (Acta Entomologica Serbica, 2019)
During a three year systematic sampling of the hoverfly fauna in highlands of western Serbia, 150 hoverfly species of 51 genera were recorded for this region. Eumerus ovatus Loew, 1848, new to the fauna of Serbia, was recorded on mountain Zlatibor. Additionally, 4 new hoverfly species from the genus Merodon Meigen, 1803 were found, awaiting species descriptions. The most species-rich areas in the investigated region are SW part of Mt. Golija and SE part of Mt. Zlatar. These mountains also have the highest number of protected and strictly protected species. In order to preserve this high local diversity of hoverflies, protection of these areas, as well as proper conservation management are of crucial importance.